Educational environment planning in improving the quality of education in Pasar Minggu 01 Morning Elementary School - Muhammad Ma'sum; Endin Mujahidin; Nesia Andriana; Smith John (At Turots: Jurnal Pendidikan Islam, 2025)
The educational environment plays an important role in creating a conducive learning atmosphere and supporting the achievement of educational goals. This article aims to analyze the condition of the educational environment at SDN Pasar Minggu 01 Pagi, identify the supporting and inhibiting factors in planning the educational environment and formulate an ideal strategy to create an educational environment that supports learning quality. The results show that the condition of the educational environment at SDN Pasar Minggu 01 Pagi still faces various challenges, such as limited facilities and lack of green space. Supporting factors include government policies and community participation, while inhibiting factors include limited budget and lack of awareness of the importance of the educational environment.